Metabologenomics analysis of Pseudomonas sp. So3.2b, an Antarctic strain with bioactivity against Rhizoctonia solani - Maimone, Naydja Moralles; Junior, Mario Cezar Pozza; de Oliveira, Lucianne Ferreira Paes; Rojas-Villalta, Dorian; de Lira, Simone Possedente; Barrientos, Leticia; Núñez-Montero, Kattia (Frontiers in Microbiology, 2023)
Phytopathogenic fungi are a considerable concern for agriculture, as they can threaten the productivity of several crops worldwide. Meanwhile, natural microbial products are acknowledged to play an important role in modern agriculture as they comprehend a safer alternative to synthetic pesticides. Bacterial strains from underexplored environments are a promising source of bioactive metabolites. In this study, we applied the OSMAC (One Strain, Many Compounds) cultivation approach, in vitro bioassays, metabolomics, and genomics analyses to investigate the biochemical potential of Pseudomonas sp. So3.2b, a strain isolated from Antarctica. Molecular networking revealed that metabolite synthesis has growth media specificity in this strain, and it was reflected in bioassay results against Rhizoctonia solani pathogen isolated from different plants. In silico tools enabled the annotation of bananamides, rhamnolipids, and butenolides-like molecules in the crude extracts, whereas potential chemical novelty was also suggested by several unidentified compounds. The genome mining confirmed a wide variety of biosynthetic gene clusters (BGC) present in this strain, with low to no similarity with known molecules. An NRPS-encoding BGC was identified as responsible for producing the banamides-like molecules, while phylogenetic analysis demonstrated a close relationship of our strain with other rhizosphere bacteria. Therefore, by combining -omics approaches and bioassay results, our study demonstrates that Pseudomonas sp. So3.2b strain has potential application to agriculture as a source of bioactive metabolites, revealing its promising biosynthetic capacity.